YouTube and Muslim Women’s Legal Subjectivities - Bouclin, Suzanne (Oñati Socio-Legal Series, 2013)
This paper is located within the discursive and spatio-temporal landscape of post 9/11 Canada in which national identity and beliefs about belonging are embedded in pervasive Islamophobia. Its starting point is that social media are key sites for expression of discrimination and intolerance vis-à-vis people of the Muslim faith, and especially the constitution of Muslim face and head scarves as a metonym for Islamic terrorism and a quintessential symbol of uniquely fundamentalist manifestation of patriarchy. I ask, however, whether new modes of visibility might be captured when we examine representational sites of Muslim femininity through the lens of ‘new’ or ‘critical’ legal pluralism. I highlight how women have used Social Networking Sites (SNSs) to respond and reconfigure more entrenched discourses around Muslim femininity circulated elsewhere, such as in formal institutionalized state-based law, mainstream/Western feminist discourses, and in popular cultural productions. I have found that Muslim women deploy social media to constitute or express alternative subjectivities and to represent and evaluate their own understandings of feminism, normative femininity, religious practices, including the multiple meanings that attach to the donning of Islamic headscarves.